ANALISIS PERKEMBANGAN TUMBUH TANAMAN KALIANDRA MERAH (Calliandra calothyrsus) DI AREAL PASCA TAMBANG TARJUN KOTABARU - Nurmala Siti Fatimah; Yudi Firmanul Arifin; Dina Naemah (Jurnal Sylva Scienteae, 2023)
The purpose of this research is to analyse the physical and chemical properties of soil in clay and laterite areas, and to analyse the average growth of diameter and height of red calliandra plants each year. The parameters used are red calliandra consisting of diameter and height, soil chemistry such as N, P, K, Mg, Fe, CEC, pH, and soil physical properties namely bulk density and sand, dust, clay. The results of soil physical properties of the volume weight of the clay area have a large bulk denstity so that the soil is denser than the laterite area. The soil texture of the clay area is dominated by clay according to the soil texture class, namely dusty clay while the laterite area is dominated by dust. Soil chemical parameters of N elements have very low criteria, P is very low-medium, K and Fe are moderate, Mg is very low and pH is slightly alkalis. The average growth of diameter and height of red calliandra in the clay area is 0.32 cm/year and 1.06 m/year which has a greater value than the laterite area.Tujuan dari penelitian ini yaitu menganalisis sifat fisik dan kimia tanah pada areal clay dan laterit, menganalisis rata-rata pertumbuhan diameter dan tinggi tanaman kaliandra merah setiap tahunnya. Parameter yang digunakan yaitu kaliandra merah terdiri dari diameter dan tinggi, kimia tanah seperti N, P, K, Mg, Fe, KTK, pH, serta fisik tanah yaitu bulk density dan pasir, debu, liat. Hasil sifat fisik tanah berat volume areal clay memiliki bulk denstity  besar sehingga tanah lebih padat dibandingkan areal laterit. Tekstur tanah areal clay  didominasi oleh liat sesuai kelas tekstur tanah yaitu liat berdebu sedangkan areal laterit didominasi debu. Parameter kimia tanah unsur N memiliki kriteria sangat rendah, P sangat rendah-sedang, K dan Fe sedang, Mg sangat rendah dan pH bersifat agak alkalis. Pertumbuhan rata-rata diameter dan tinggi kaliandra merah areal clay yaitu 0,32 cm/tahun dan 1,06 m/tahun memiliki nilai lebih besar dibandingkan areal laterit.